Defining the cultured and uncultured bacterial fractions in Cannabis seeds - Carolina Lobato; Ahmed Abdelfattah; Gabriele Berg; Tomislav Cernava (Environmental Microbiome)
Abstract Background Seeds provide a unique environment shaped by co-evolutionary processes, hosting diverse microbial communities. While microbiome studies have uncovered an extensive diversity of microorganisms, culture-based approaches remain crucial for understanding microbial potential and functional interactions. However, the factors influencing microbial culturability within seeds are not well understood. Results In this study, we investigated the culturing patterns of bacteria inside Cannabis seeds, assessing their phylogenetic diversity, abundance, and putative interactions. Bacteria were cultured from 54 different Cannabis accessions using germinated seeds and a range of nutrient media including those supplemented with Cannabis extracts. The cultured fraction consisted of taxa from five prominent classes—Gammaproteobacteria, Bacilli, Actinobacteria, Alphaproteobacteria, and Bacteroidia—encompassing 36 genera. Despite representing only 6.3% of the total microbiota, these cultured bacteria accounted for 89.2% of the microbial population. Almost 60% of the amplicon sequence variants (ASVs) were phylogenetically distant from cultured taxa. Rare bacterial groups such as Acidobacteriae and Verrucomicrobiae, known for their plant growth-promoting traits, were exclusively found in the uncultured fraction. Network analyses revealed that uncultured taxa are centralized and more connected to hubs, suggesting that interspecies interactions strongly influence culturability. Conclusion Our findings highlight the limitations of culture-based methods in capturing the full microbial diversity of Cannabis seeds and emphasize the importance of microbial interactions in determining culturability. The strong network connectivity of uncultured taxa suggests that interdependencies and competition within the seed microbiome may hinder the isolation of key bacterial groups. These insights provide a framework for refining cultivation strategies to recover ecologically significant microbes with potential agricultural applications.